Experiential Marketing Strategies in Luxury Restaurants : A Pythagorean Fuzzy AHP Approach - Das, Sweety; Gupta, Neha; Kumar, Vinod; Yadav, Rajesh Kumar (Indian Journal of Marketing, 2025)
Purpose : The current study had the objective of determining and ranking experiential marketing strategies embraced by luxury restaurants in India. With the age of customer experience being the differentiator in the present time, luxury food brands need to know which strategies are most important. Design/Methodology/Approach : Twelve experiential marketing strategies were extracted from a comprehensive literature review. The strategies were validated by expert opinion using the Pythagorean Fuzzy Delphi method. A panel of five experts in restaurants administered a structured questionnaire. The relative importance of the strategies was then computed using the Pythagorean Fuzzy Analytical Hierarchy Process. Findings : The research found that virtual and augmented reality experiences, exclusive distribution, and free sample provision were rated as the most important tactics for luxury restaurants. These tactics were rated the highest on the perceived value scale by experts in the industry. Gift promotion, food quality experience, and electronic word of mouth were other successful tactics. Practical Implications : The findings offer helpful insights into marketing strategists and managers operating in the luxury food sector. By prioritizing the top-ranked experiential strategies, companies could drive greater customer engagement, brand loyalty, and market differentiation. The research emphasized the importance of innovative, immersive, and emotionally engaging customer experiences. Originality/Value : This research contributed to the limited empirical literature on experiential marketing in India's luxury restaurants and employed an integrated fuzzy multi-criteria decision-making framework to derive actionable intelligence from expert opinion.